Massive Open Online Course (MOOC): A New Online Learning Approach to LIS Professionals - Kaushik, Anna (Library Waves, 2015)
This study defines the concept of Massive Open Online Course (MOOC) and argues regarding involvement of library and information science professionals in MOOC environment. This study also presents steps required in creation of a MOOC and a comparison of different MOOC platforms. This study may be helpful in knowing-how of the Massive Open Online Course (MOOC) in details.